Number of medical consultations at Australian Antarctic stations, 1986-2019 - AYTON, JEFF (hasPrincipalInvestigator); AYTON, JEFF (processor); Australian Antarctic Data Centre (publisher)
This dataset was originally set up as a "State of the Environment" indicator - however, that application no longer functions at the Australian Antarctic Data Centre, so the data have been extracted and attached to this original metadata record for the indicator. Information was obtained from the ANARE Health Register. See Metadata record entitled ANARE Health Register. INDICATOR DEFINITION The rates of illness and injury per 1000 person years in all continental Antarctic stations and Macquarie Island. RATIONALE FOR INDICATOR SELECTION Human health can be an indicator of the natural and man-made environment. Some of the factors affecting human health can be directly related to the quality of the environment. Monitoring the rate of medical consultations in Antarctica can provide useful baseline information on illness and injury rates, and potentially provide insight into health trends due to Antarctic conditions. In Antarctica the man-made environment is of particular importance due to the highly adverse nature of the natural environment and as a surrogate for the isolation of outer space. Without dwellings and support structures human habitation of Antarctica would be impossible. The interaction between people and the natural environment is also worthy of attention. The rate of various injuries and illnesses can be attributed, at least in part, to the severe conditions present in the Antarctic. Antarctica also provides useful data on the effects of isolated and confined environments (ICE) on human health. There are some straightforward examples of direct relationships between environmental factors and human health. However, multiple causation and the complexity of mediating processes mean that it is typically difficult to relate specific 'environmental' inputs to particular health outcomes. DESIGN AND STRATEGY FOR INDICATOR MONITORING PROGRAM Spatial scale: Australian Antarctic and sub-Antarctic stations Frequency: Monthly figures reported annually Measurement Technique: Time series information to determine trends in medical consultations. Information was obtained from the ANARE Health Register. See Metadata record entitled ANARE Health Register. RESEARCH ISSUES Due to the unique nature of the environment and the expeditioners residing in Antarctica, comparison with similar groups elsewhere would be valuable. The database has reached sufficient size to justify closer analysis of data that may discern trends in health and provide a better picture of the effects of the Antarctic environment. Trends may not be obvious and may have a considerable impact on human activities in the Antarctic. Does the presence of people and potential pathogens influence the rate of disease among populations of Antarctic wildlife?